Analysis of the Effectiveness of the Complete Systematic Land Registration Program (PTSL) in Pemalang Regency - Ilham Helsa Ardiansyah (Faculty of Law, Universitas Negeri Semarang, 2025)
The strategic policy program of Complete Systematic Land Registration aims to provide legal certainty and protection of land rights to the community. The implementation of PTSL faces various obstacles that affect the effectiveness of the program, including in Pemalang Regency. This research aims to analyze the effectiveness of the implementation of PTSL, identify internal and external technical and non-technical obstacles and formulate legal solutions to overcome these obstacles. This study uses a qualitative method with a juridical-empirical approach, collecting data through in-depth interviews and official documents. Key findings show that although the PTSL program has successfully achieved most of the land certification targets, technical and non-technical constraints are still significant, especially in terms of human resources, availability of procurement of goods and transportation, road infrastructure, the presence of individuals who hinder the PTSL program, and public understanding. This study emphasizes that a complete systematic registration program can have an effect on reducing land disputes and providing legal certainty for land by issuing land certificates.